Genetic manipulation of agronomically important traits in Lilium - Núñez de Cáceres González, Francisco Federico (2013)
The ornamental industry has become an important economic force in recent years, in the UK alone this industry is estimated to be around £2.1 billion, while the international trade is around £60-75 billion (Chandler and Tanaka, 2007). The continued success of the floriculture industry depends on the introduction of new species/cultivars with major alterations in key agronomic characteristics, such as resistance to pathogens, novel flower colour and patterns or control of male fertility. Lilium, one of the most important bulbous ornamental crops, is an attractive and popular cut flower. However, the production of vast quantities of pollen that stains easily and is toxic to animals is not always desirable. The control of pollen release without affecting the appearance of the flower is therefore an important breeding goal. Lilium is also susceptible to several fungal pathogens, including Botrytis cinerea, which infects leaves, stem and flowers leading to a reduction of yield. New cultivars have tended to rely upon selective breeding as a mechanism for trait development. However approaches that utilise transgenes to manipulate traits of interest provide alternative opportunities for the ornamental industry provided that transformation and regeneration can be achieved efficiently.